Frank Lloyd Wright's Fallingwater - Zipf, Catherine W., author.
1 online resource
Keywords: "Frank Lloyd Wright's Fallingwater explores the relationship between the economic tumult in the United States in the 1930s, Frank Lloyd Wright, and the construction of his most famous house, Fallingwater. The book reinterprets the history of this iconic building, recognizing it as a Depression-era monument that stands as a testimony to what an American architect could achieve with the right site, client, and circumstance, even in desperate economic circumstances. Using newly available resources, author Catherine W. Zipf examines Wright's work before and after Fallingwater to show how it was influenced by the economic climate, public architectural projects of the Great Depression, and America's changing relationship with Modernist style and technology. Including over 50 black and white images, this book will be of great interest to students, historians, and researchers of art, architecture, and Frank Lloyd Wright"--